(untitled) (Proceedings of Southern Federal University. Philology, 2024)
DOI 10.18522/1995-0640-2024-1-114-122 The subject of research are the antique motives that occur in the works of A. Mire, not well-known woman writer of the Silver Age of Russian literature. The antique characters appearing in a number of her stories (the poet Sappho, a Roman dictator, the sculptor Phidias) and the antiquity which serves as a background in the analyzed texts allows the writer to depict “timeless” situations: the jealousy of a distressed woman, the ecstatic inspiration of a genius, the human greediness and thirst for goods of the Earth. Key words: A. Mire, Menander, Publius Ovidius Naso, Gaius Julius Caesar, Phidias, Prometheus, antiquity, the myth of Sappho, hetaera Acknowledgments: The author expresses gratitude to his scientific supervisor, Ph.D., Prof. Mikhailova Maria Viktorovna, as well as Konovalova Tatyana Vladimirovna and Alikin Pavel Sergeevich.